Low airborne tenacity and spread of ESBL‐/AmpC‐producing Escherichia coli from fertilized soil by wind erosion. (2nd March 2021) - Siller, Paul; Daehre, Katrin; Rosen, Kerstin; Münch, Steffen; Bartel, Alexander; Funk, Roger; Nübel, Ulrich; Amon, Thomas; Roesler, Uwe
Summary: ESBL‐/AmpC‐producing Escherichia coli from organic fertilizers were previously detected on soil surfaces of arable land and might be emitted by wind erosion. To investigate this potential environmental transmission path, we exposed ESBL‐/AmpC‐positive chicken litter, incorporated in agricultural soils, to different wind velocities in a wind tunnel and took air samples for microbiological analysis. No data exist concerning the airborne tenacity of ESBL‐/AmpC‐producing E . coli . Therefore, we explored the tenacity of two ESBL/AmpC E . coli strains and E . coli K12 in aerosol chamber experiments at different environmental conditions. In the wind tunnel, ESBL/AmpC‐producing E . coli were detected in none of the air samples ( n = 66). Non‐resistant E . coli were qualitatively detected in 40.7% of air samples taken at wind velocities exceeding 7.3 m s −1 . Significantly increased emission of total viable bacteria with increasing wind velocity was observed. In the aerosol chamber trials, recovery rates of airborne E . coli ranged from 0.003% to 2.8%, indicating a low airborne tenacity. Concluding, an emission of ESBL/AmpC E . coli by wind erosion in relevant concentrations appears unlikely because of the low concentration in chicken litter compared with non‐resistant E . coli and their low airborne tenacity, proven in the aerosol chamber trials.